2014
DOI: 10.1002/mawe.201400231
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and mechanical properties of high power diode laser (HPDL) treated cast aluminium alloys

Abstract: The appliance and development of modern technologies in the areas of surface engineering can be extended by laser surface treatment, especially using high power diode laser (HPDL) for remelting, feeding and/or alloying. The purpose of this work was to determine technological and technical conditions for tungsten carbide (WC) ceramic powder feeding into the surface layer of the laser treated Al-Si-Cu cast aluminium alloys with high power diode laser, as well as to investigate the microstructure and ceramic powd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
7
3

Relationship

5
5

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 15 publications
0
26
0
Order By: Relevance
“…Currently, the concept of functional lightweight materials is a priority and the most investigated worldwide field of material science and engineering concerning the production and processing of new developed engineering materials. Previous studies about the effects of laser beam effect on various materials, including magnesium alloys as well as tool steels, based on the authors own long-term investigation, summarizing the experience of laser surface treatment reveal that, there are chemical composition and structure changes which are different from those occurring during conventional heat treatment [9,[17][18][19][20][21][22][23][24][25][26][27]. This causes, that the laser treated elements shows higher hardness (especially for TaC alloyed steel surface - Fig.…”
Section: Investigation Resultsmentioning
confidence: 99%
“…Currently, the concept of functional lightweight materials is a priority and the most investigated worldwide field of material science and engineering concerning the production and processing of new developed engineering materials. Previous studies about the effects of laser beam effect on various materials, including magnesium alloys as well as tool steels, based on the authors own long-term investigation, summarizing the experience of laser surface treatment reveal that, there are chemical composition and structure changes which are different from those occurring during conventional heat treatment [9,[17][18][19][20][21][22][23][24][25][26][27]. This causes, that the laser treated elements shows higher hardness (especially for TaC alloyed steel surface - Fig.…”
Section: Investigation Resultsmentioning
confidence: 99%
“…An intensive development of technology causes continuous increase of a wide base of research methods such as: atomic force microscopy (AFM) [5,6], scanning electron microscopy (SEM) [7,8] and X-ray diffraction (XRD) [7][8][9][10][11][12][13][14][15]. Especially methods such as XRD or SEM are widely used for analysis of the oxide layers [4,7,11,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In the work [5] there was confirmed that the mechanical properties of the ZnAl alloy primarily affect the distance between dendrites arms, instead of the grain size. Primarily the dendrite arm spacing and distribution of intermetallic phases influences the mechanical properties of the Zn-Al alloys, instead of the grain size [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%